Individual and Organizational Variables in Job Satisfaction of First- to Ninth-Grade Teachers: A Preferred Reporting Items for Systematic Reviews and Meta-Analyses-Guided Scoping Review - Raiany Poloni; Célia Oliveira; João Lopes (Education Sciences)
(1) Background: Teacher job satisfaction is critical to a school’s organizational development and students’ academic success. This study investigates the job satisfaction of first- to ninth-grade teachers, focusing on the individual and organizational variables that influence and explain this phenomenon. (2) Methods: A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines, analyzing studies published between 2017 and 2022 in the Scopus, ERIC, and SciELO databases. A total of 32 studies were included in the review. (3) Results: The results indicate that demographic variables (33.5%) are the most frequently examined at the individual level concerning teacher job satisfaction. At the organizational level, variables associated with school principals are the most prominently represented (12%). (4) Conclusions: This review identifies a significant gap in the literature, with limited attention to individual and organizational variables. This finding underscores the need for further research on emerging factors, such as the impact of administrative burdens on teacher satisfaction. Additionally, this study highlights the importance of accounting for different countries’ socio-cultural and institutional contexts when exploring factors that influence teacher job satisfaction.